PEMBELAJARAN PEMECAHAN MASALAH MATEMATIKA DI SEKOLAH DASAR: MASALAH DAN UPAYA YANG DAPAT DILAKUKAN - Carolina Santi; Arnoldus Helmon; Eliterius Sennen (Jurnal Literasi Pendidikan Dasar (JLPD), 2021)
The mathematical problem solving ability of elementary school students in Indonesia is still low, which is confirmed through a number of surveys or research. This indicates that there are problems that occur in the learning process of solving math problems in elementary school. This study aims to describe problems of problem solving instruction and efforts to improve students' ability in solving mathematics problems in elementary school. This research is a library research that use books and articles as main data resources. Data analysis was carried out using descriptive analytical methods and comparative analysis methods. The results of this study indicate that the problems faced in learning mathematics problem solving in elementary schools are: 1) teachers lack emphasis on problem solving, 2) teachers experience misconceptions related to problem solving, 3) teachers have difficulty in teaching problem solving, 4) teachers still applying the teacher centered learning model, and 5) teachers' erroneous perceptions about problem solving and learning so that it has implications for their learning. Efforts to improve students' ability in solving mathematical problems in elementary school are: 1) innovating mathematics learning, namely implementing mathematics learning with problem solving, 2) giving non-routine questions as a way to improve problem solving abilities of elementary school students, 3) familiarize students with applying problem-solving steps directed through metacognitive guidance techniques, and 4) teachers must strive for learning using learning models that can provide opportunities and encourage students to practice students' mathematical problem solving skills.